(untitled) (Raparin Journal of Humanities (RJH), 2025)
On development of public opinions on the accidents that happen in Kurdistan region, The study relied on the descriptive approach, using the newspaper survey tool to collect and analyze it by survey form, The population of the research incudes:( Kurdish writers in politics field) are taken as a sample for the research. The most important goal of the research is knowing the role of Iraqi channel on development of public opinions about the accidents and events that happen in Kurdistan region and to which extent they provoked public opinions on the recent subjects and accidents. the most important outcomes that the researchers achieved include: Kurdish Iraqi channel did not give much attention to the events and accidents of Kurdistan region and hence could not become an effective channel on development of public opinions. Even though Kurdish Iraqi channel is a Kurdish channel, but it cared very little about the different accidents and events that happened in Kurdistan region, when in fact it could actually give more attention and importance to the political, economical, social and health events and that happen inside Kurdistan region.